RELIABILITY AND ECONOMY OF NAVIGATION ERGATIC SYSTEMS (Perner's Contacts, 2017)
The process link of the aircraft and the human (pilot-operator) information system is realized by transferring a given or newly created event with known coordinates (x0, t0) to the desired position s0, with coordinates (x, y, z) at time t≥t0 with the previously known accuracy and security. Aviation producers pay considerable attention to increasing safety and accuracy as well as the economic advantage of aircraft navigation ergatic systems. The definition of safety also includes the definition of reliability of the faultless operation of the navigation ergatic system that is necessary to ensure that the aircraft's on-board system is at the highest level of safety operation. The definition of reliability is defined by the probability that has evaluated the navigation ergatic system. The reliability will not solve the problems what will happen if the system fails. In this case, a person (pilot-operator) enters the process of ergatic navigation, which usually solves statistically defined cases, determined by the mentioned relationships and to ensure the reliable operation of navigation ergatic systems.conventional coefficients of relationship: human - object (aircraft). This paper designs the cost model, which is usable for the above-
Keywords: reliability; on-board system; navigation ergatic systems; pilot/operator; efficiency; workload; cost